Zinc supplementation induces apoptosis and enhances antitumor efficacy of docetaxel in non-small-cell lung cancer - Kocdor, Hilal; Ates, Halil; Aydin, Suleyman; Cehreli, Ruksan; Soyarat, Firat; Kemanli, Pinar; Kocdor, Mehmet Ali (Dove Medical Press Ltd, 2015)
Background: Exposure to exogenous zinc results in increased apoptosis, growth inhibition, and altered oxidative stress in cancer cells. Previous studies also suggested that zinc sensitizes some cancer cells to cytotoxic agents depending on the p53 status. Therefore, zinc supplementation may show anticancer efficacy solely and may increase docetaxel-induced cytotoxicity in non-small-cell lung cancer cells. Methods: Here, we report the effects of several concentrations of zinc combined with docetaxel on p53-wild-type (A549) and p53-null (H1299) cells. We evaluated cellular viability, apoptosis, and cell cycle progression as well as oxidative stress parameters, including superoxide dismutase, glutathione peroxidase, and malondialdehyde levels. Results: Zinc reduced the viability of A549 cells and increased the apoptotic response in both cell lines in a dose-dependent manner. Zinc also amplified the docetaxel effects and reduced its inhibitory concentration 50 (IC50) values. The superoxide dismutase levels increased in all treatment groups; however, glutathione peroxidase was slightly increased in the combination treatments. Zinc also caused malondialdehyde elevations at 50 mu M and 100 mu M. Conclusion: Zinc has anticancer efficacy against non-small-cell lung cancer cells in the presence of functionally active p53 and enhances docetaxel efficacy in both p53-wild-type and p53-deficient cancer cells.
Keywords: lung cancer; zinc; docetaxel; A549; H1299